Literasi Rukti Jenazah: Membangun Kesadaran Kolektif Masyarakat Desa Wani 2 Kecamatan Tanantovea. - Sutan Nokoe, Nurhayati; Syamsuddin; Rosnani Lakuna (Legal Empowerment: Jurnal Pengabdian Hukum, 2024)
Death is an inevitable reality of life. In Islam, the process of taking care of a corpse (rukti corpse) is fardhu kifayah, a collective obligation that is terminated if it has been carried out by some of the congregation. This service examines the community's awareness and skills in carrying out corpse rukti. The partners for this service are the people of Wani 2 Village, Tanantovea District, Donggala Regency. Even though the majority are Muslims, the local community's knowledge and skills regarding this process are still very limited. This creates challenges in carrying out these fardhu kifayah obligations adequately, especially during emergency situations or consecutive deaths. The methodology used in this service includes material presentation, practical simulations, and evaluation. The results of the service showed that the training held had increased the participants' knowledge and skills in the process of washing, shrouding, praying, and burying bodies according to Islamic law. This study recommends the need for permanent institutions for training in corpse rukti as well as the active involvement of all members of society, not just religious teachers and sharia officials, to increase their understanding and ability to care for corpses, in line with humans' position as caliphs on earth that does not end with physical death.